Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

a=(vf-vi)/t solve for t
solve for vi 
solve for vf


Sagot :

AL2006
A = (vf - vi) / t    <== call this the "given equation"

=====================================

For t :

Multiply each side of the given equation by 't' :    A t = (vf - vi)

Divide each side by 'A' :                                        t = (vf - vi) / A

=====================================

For vi :

Multiply each side of the given equation by 't' :    A t = (vf - vi)

Subtract ' vf ' from each side:                             A t - vf = -vi

Multiply each side by  -1 :                                  vf - A t = vi
=====================================

For vf :

Multiply each side of the given equation by 't' :    A t = (vf - vi)

Add ' vi ' to each side:                                      A t + vi = vf